The effects of players` rotations on high-intensity activities in professional futsal players - Ribeiro, J. N.; Yousefian, F.; Illa, J.; Couceiro, M.; Sampaio, J.; Travassos, B. (Journal of Human Kinetics, 2024)
The current study aimed to investigate the effects of interchange rotations on players` physical performance during competition, with special reference to high-intensity activity (HIA) according to the playing position. Physical performance data, collected from 19 professional players during seven official matches from the Spanish futsal league using a portable local positioning system, included the number of high-speed running activities (>18 km·h-1), high-intensity accelerations (>3 m·s-2), and high-intensity decelerations (>3 m·s-2). Statistically significant (p = 0.05) differences were observed in the number of HIA efforts across rotations and between positions. Players performed more HIA efforts in the first rotation (n = 17.6), suggesting that their first rotation was more demanding than all subsequent rotations. Wingers demonstrated a higher HIA effort and frequency of HIA efforts when compared to defenders (p = 0.05) and pivots (p = 0.001). For all positions, the first rotation was more physically demanding as the number of HIA efforts per rotation decreased with an increased number of rotations throughout the match. Furthermore, higher HIA profile positions, such as wingers and defenders, were less likely to maintain consistent HIA properties (repetition number, time-frequency, and the work-rate) across subsequent rotations during the match. The findings of the study can inform coaching decisions regarding players` rotations to maintain consistent HIA performance throughout the match.